Measuring student experience : relationships between Teaching Quality Instruments (TQI) and Course Experience Questionnaire (CEQ) : resource document. - Hirschberg, Joe; Lye, Jenny (University of Melbourne. Dept of Economics, 2011)
Appendices to the main report published as a separate document and called a resource document. Consists of seven appendices covering the following topics: institutional practices - TQIs from Australian tertiary institutions; data for the analysis of Australian TQIs; description of new survey instruments; form of the CEQ/GDS questionnaire; distance matrix for responses to CEQ and new TQI survey; descriptions of data used in Chapter 5; results by dependent variables across models.